Patterns of planning and implementation of PJOK curriculum in elementary schools in the post-COVID-19 pandemic period - Mohammad Faruk; Mohammad Ali; Rudi Susilana; Laksmi Dewi; Norlidah Alias; I Made Sriundy M; Imam Syafi’i (Inovasi Kurikulum)
Learning planning must be adjusted to students’ conditions to achieve educational goals. The COVID-19 pandemic brought significant changes requiring high adaptability, especially in education. This study aims to identify planning and implementation patterns of the Physical Education and Health (PJOK) curriculum in elementary schools during the post-COVID-19 pandemic. Using a descriptive survey method, the research explored how PJOK teachers plan and implement home-based learning during this period. Data was collected via a Google Forms questionnaire from 33 PJOK teachers who participated in a Focus Group Discussion on post-pandemic curriculum planning. The study’s findings reveal that most teachers adjusted their planning based on the available facilities and infrastructure in students' homes. The curriculum was simplified to emphasize life skills relevant to the post-pandemic context. Implementing the PJOK curriculum requires collaboration with parents to monitor and support student learning at home. Teachers predominantly use WhatsApp to deliver instructional materials and rely on YouTube as a learning resource. This research highlights the need for adaptive curriculum strategies that accommodate challenges in post-pandemic education while ensuring effective learning despite limited resources.